Powerful writing structures : brain pocket strategies for supporting a year-long writing program - Gear, Adrienne (Pembroke, 2020)
"This timely book uses thinking structures to deepen student writing. It revolves around "brain pockets" to help students appreciate the qualities of different writing forms. Some powerful examples include memory pockets for personal narrative writing, fact pockets for nonfiction, and imagination pockets for story writing. Detailed lesson plans are featured along with sample anchor books and book lists. Based on extensive classroom testing, student samples throughout the book illustrate this unique approach to teaching writing. Suggestions for setting up an effective writing program and assessment tips for guiding instruction, complete this comprehensive approach to developing a year-long writing program."--